Religion as a Language: Exploring Alternative Paths in Conversation with Postreductionist Anthropologies - Oviedo Torró, Lluís (Zygon, 2015)
New scientific approaches to religion have delivered a considerable number of theories aimed at explaining it, despite its cognitive and adaptive oddities. These efforts were built on available theoretical frameworks, including those from cognitive science, biology, and anthropology. Many voices have raised criticism against several aspects in the cognitive and evolutionist program, even if recognizing their legitimacy and the fruits collected to date. A pressing issue is whether the problem with the new scientific study of religion is related, to some extent, to the use of outdated views on human evolution, mind, and behavior. If this is the case, then a deep revision concerning current models is required. The new direction proposed should account for more complex aspects of human nature following multilevel models, and a specific human feature—language—that could better explain religion as a meaning system. Understanding religion as a language might open an alternative path inside cognitive studies that is closer to how it is lived by believers.